Pseudomonas aeruginosa reference strains PAO1 and PA14: A genomic, phenotypic, and therapeutic review - Grace, Amber; Sahu, Rajnish; Owen, Donald R.; Dennis, Vida A. (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is a ubiquitous, motile, gram-negative bacterium that has been recently identified as a multi-drug resistant pathogen in critical need of novel therapeutics. Of the approximately 5,000 strains, PAO1 and PA14 are common laboratory reference strains, modeling moderately and hyper-virulent phenotypes, respectively. PAO1 and PA14 have been instrumental in facilitating the discovery of novel drug targets, testing novel therapeutics, and supplying critical genomic information on the bacterium. While the two strains have contributed to a wide breadth of knowledge on the natural behaviors and therapeutic susceptibilities of P. aeruginosa, they have demonstrated significant deviations from observations in human infections. Many of these deviations are related to experimental inconsistencies in laboratory strain environment that complicate and, at times, terminate translation from laboratory results to clinical applications. This review aims to provide a comparative analysis of the two strains and potential methods to improve their clinical relevance.